Monitoring MSME Data That Has Been Certified On The Jakpreneur Platform Using Tableau Public - Tri Wahyudi; Devi Puspita Sari; Vara Maulidyah Hidayah; Yuliana Bachtiar; Piqih Akmal (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This research aims to enhance the monitoring of certified Micro, Small, and Medium Enterprises (MSMEs) on the Jakpreneur platform through the implementation of effective data visualization techniques. The study involves the collection and integration of MSME certification data from Jakpreneur , and utilizes Tableau Public, a data visualization tool, for in-depth analysis and visualization. The objective is to gain comprehensive insights into the progress, geographical distribution, and distinctive features of registered MSMEs. This monitoring system is designed to empower stakeholders to make informed decisions related to the development and support of MSMEs. By showcasing the application of data visualization technology in the context of local micro-business certification, this research contributes not only to the efficiency of MSME monitoring but also serves as a model for using such technology in similar scenarios